1999
DOI: 10.1002/(sici)1521-3935(19990601)200:6<1446::aid-macp1446>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of poly(dihexylsilane) embedded in Langmuir-Blodgett multilayers of arachidic acid

Abstract: Poly(dihexylsilane) (PDHS) and arachidic acid (AA) were co-spread onto a cadmium-containing water subphase and transferred onto a solid substrate as multilayers by the Langmuir-Blodgett method. The structure of these films was evaluated by means of UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffractometry, and film thickness measurements. The results indicated that the PDHS ultrathin film is incorporated into a well-structured AA multilayer matrix without apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Earlier works have shown that successful LB deposition of other functional hydrophobic polymers, poly(alkylthiophenes) 13 and the vinyl copolymers with pendant chromophores, can be achieved when mixed with a long-chain fatty acid. We have also reported the formation of ultrathin PDHS film on an arachidic acid monolayer at the air/water interface and their LB deposition . Because of the poor miscibility of PDHS with arachidic acid, the contribution of PDHS to the lateral area in the monolayer was minor, showing a slight area increase at lower pressure regions in the π− A isotherms .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Earlier works have shown that successful LB deposition of other functional hydrophobic polymers, poly(alkylthiophenes) 13 and the vinyl copolymers with pendant chromophores, can be achieved when mixed with a long-chain fatty acid. We have also reported the formation of ultrathin PDHS film on an arachidic acid monolayer at the air/water interface and their LB deposition . Because of the poor miscibility of PDHS with arachidic acid, the contribution of PDHS to the lateral area in the monolayer was minor, showing a slight area increase at lower pressure regions in the π− A isotherms .…”
Section: Resultsmentioning
confidence: 92%
“…In this sense, the mixed films can be dubbed as “hybrid” films. In the case of mixing with a long-chain fatty acid, on the other hand, the mixed film gave only a slight expansion at low pressures in the π− A curve and did not show such systematic expansions with R . Cospread monolayers of polymer/fatty acid systems exhibit π− A isotherms characteristic of a phase separation of the two components. ,, …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Fully hydrophobic soluble polymers such as polystyrene and polysilanes (Si-catenated polymers) having hydrocarbon substituents cannot be applied. Some attempts of LB deposition have been made for such polymers by mixing with monolayer-forming long chain carboxylic acid, , nevertheless the polymers are segregated within the LB films 11b and the monolayer spreading of such polymers has not been realized.…”
mentioning
confidence: 99%